2021
DOI: 10.1002/cam4.3887
|View full text |Cite
|
Sign up to set email alerts
|

Competing risk nomogram predicting cancer‐specific mortality for endometrial cancer patients treated with hysterectomy

Abstract: BackgroundThe incidence of endometrial cancer has tended to increase in recent years. However, competing risk nomogram combining comprehensive factors for endometrial cancer patients treated with hysterectomy is still scarce. Therefore, we aimed to build a competing risk nomogram predicting cancer‐specific mortality for endometrial cancer patients treated with hysterectomy.MethodsPatients diagnosed with endometrial cancer between 2010 and 2012 were abstracted from the Surveillance, Epidemiology, and End Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Those aged over 80 years had a high risk and a shorter OS (50–59 years: hazard ratio [HR] 1.93, 95% confidence interval [CI] 1.61–2.32; ≥80 years: HR 8.39, 95% CI 6.98–10.07). This finding was consistent with the results of other studies, 8,10,11 except for Bendifallah et al, 9 who indicated by a nomogram that the level of evidence for an association with OS for age was inconclusive. Research by Kang et al 12 showed that para‐aortic lymph node metastasis was not associated with age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Those aged over 80 years had a high risk and a shorter OS (50–59 years: hazard ratio [HR] 1.93, 95% confidence interval [CI] 1.61–2.32; ≥80 years: HR 8.39, 95% CI 6.98–10.07). This finding was consistent with the results of other studies, 8,10,11 except for Bendifallah et al, 9 who indicated by a nomogram that the level of evidence for an association with OS for age was inconclusive. Research by Kang et al 12 showed that para‐aortic lymph node metastasis was not associated with age.…”
Section: Discussionsupporting
confidence: 92%
“…The Kaplan–Meier curve showed that FIGO Stage had a significant impact on OS, which was consistent with Yan et al's External verification, 8 who found that tumor size is associated with OS. The result of FIGO Stage was also consistent with research by Bendifallah et al 9 The histology results were not consistent with Xie et al's research, 10 the carcinoma had a larger patient population and was related to a shorter OS. In the process of developing the nomogram, we found that age played a pivotal role in total points.…”
Section: Discussionsupporting
confidence: 68%
“…This was necessary because the traditional staging classification, commonly used for survival prediction and clinical strategies for cancer patients, cannot accurately and consistently distinguish the difference in survival among various stages. The nomogram is a comprehensive, accurate, and useful predictive model that has been used for many types of malignancies [ 25 ]. In this study, five independent prognostic factors, age, race, tumor size, grade, and radiotherapy, identified through univariate and multivariate Cox regression analyses, were engaged in the clinical nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…This study also has certain limitations. Firstly, tumor size has been identified as an independent prognostic factor in endometrial cancer and somewhat suggests a possible correlation with survival in patients with chordoma [27]. Due to the large percentage of missing information (39.2% in the original data), the present study, unfortunately, did not include the above indicator.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that spinal and pelvic chordoma is most prevalent in people over the age of 40, who often have more chronic underlying diseases and therefore have competing risks that should not be ignored. Up to now, competing-risk-based prognostic nomograms have been constructed in remarkable amounts of cancers, such as endometrial cancer, spinal and pelvic chondrosarcoma, maxillary sinus carcinoma, and primary fallopian tube carcinoma [27][28][29][30]. Nonetheless, there is a lack of research on the use of competing risk model to construct nomogram to assess survival outcomes in patients with spinal and pelvic chordoma.…”
Section: Introductionmentioning
confidence: 99%